Cephalometric evaluation after two-stage palatoplasty combined with a Hotz plate: a comparative study between the modified Furlow and Widmaier–Perko methods. Issue 5 (May 2017) - Madachi, K.; Takagi, R.; Asahito, T.; Kodama, Y.; Ominato, R.; Iida, A.; Ono, K.; Saito, I.
Abstract: The effects on craniofacial growth of two different soft palate repair techniques in two-stage palatoplasty were investigated. This was a retrospective, cross-sectional cohort study of 68 children with non-syndromic, complete unilateral cleft lip and palate. Thirty-four patients were treated with the modified Furlow method (F-group) and the remaining 34 with the Widmaier–Perko method (P-group). Craniofacial growth was assessed by analyzing 12 angular and 12 linear measurements on lateral cephalograms. Composite facial diagrams from the two groups were compared with those of a control non-cleft group. Angular and linear measurements did not differ significantly between the two groups, implying that the craniofacial morphology was not affected by the difference in soft palate repair technique. However, small differences in anterior nasal spine and posterior nasal spine were found in cleft patients compared with controls. These findings suggest that the modified Furlow and Widmaier–Perko methods have a similar impact on craniofacial growth. Considering speech function, the modified Furlow method provides better craniofacial growth and speech function. However, the long-term effects of both methods on craniofacial growth after growth cessation remain to be determined.